Imaging Organophosphate and Pyrophosphate Sequestration on Brucite by in Situ Atomic Force Microscopy. - Wang, L.; Putnis, C.; King, H.; Hövelmann, J.; Ruiz-Agudo, E.; Putnis, Andrew (American Chemical Society, 2016)
In order to evaluate the organic phosphorus (OP) and pyrophosphate (PyroP) cycle and their fate in the environment, it is critical to understand the effects of mineral interfaces on the reactivity of adsorption and precipitation of OP and PyroP. Here, in situ atomic force microscopy (AFM) is used to directly observe the kinetics of coupled dissolution-precipitation on cleaved (001) surfaces of brucite [Mg(OH)2] in the presence of phytate, glucose-6-phosphate (G6P) and pyrophosphate, respectively. AFM results show that the relative order of contribution to mineral surface adsorption and precipitation is phytate > pyrophosphate > G6P under the same solution conditions and can be quantified by the induction time of OP/PyroP-Mg nucleation in a boundary layer at the brucite-water interface. Calculations of solution speciation during brucite dissolution in the presence of phytate or pyrophosphate at acidic pH conditions show that the solutions may reach supersaturation with respect to Mg5H2Phytate.6H2O as a Mg-phytate phase or Mg2P2O7 as a Mg-pyrophosphate phase that becomes thermodynamically stable before equilibrium with brucite is reached. This is consistent with AFM dynamic observations for the new phase formations on brucite. Direct nanoscale observations of the transformation of adsorption/complexation-surface precipitation, combined with spectroscopic characterizations and species simulations may improve the mechanistic understanding of organophosphate and pyrophosphate sequestration by mineral replacement reactions through a mechanism of coupled dissolution-precipitation occurring at mineral-solution interfaces in the environment.